Perlindungan Hukum Pekerja Swasta di Kota Bandung yang Menanggung Penuh Iuran BPJS Ketenagakerjaan - Raden Qaulika Shafa Hermawan; Catharina Dewi Wulansari (POLITEKNIK KETENAGAKERJAAN, 2025)
This study aims to analyze the legal protection for private sector workers in Bandung who bear the full contribution of BPJS Ketenagakerjaan, as well as to identify the workers’ rights that are violated due to the company’s non-compliance in paying contributions. The scope of the study includes private sector workers whose contributions are fully borne by themselves, company practices, and the legal mechanisms available to workers. This research uses a descriptive qualitative approach with a case study, relying on interviews with one worker as primary data and the analysis of legal documents and local and national journal literature as secondary data. The results indicate that workers face various challenges, including limited legal knowledge, restricted access to legal assistance, complicated claim procedures, and fear of losing their jobs, causing many workers to hesitate in claiming their rights. Company practices that fail to pay full contributions violate legal provisions and create socio-economic risks for workers, including the loss of benefits from Old-Age Security, Pension Security, and Work Accident Compensation. The study concludes that there is a need to enhance worker rights education, strengthen government supervision, simplify claim procedures, and provide legal assistance so that legal protection for private sector workers can be effective and fair.